2007
DOI: 10.1111/j.1365-2141.2007.06686.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma plasma cells show different chemokine receptor profiles at sites of disease activity

Abstract: Chemokines and their receptors play a pivotal role in the regulation of B-lymphocyte trafficking. This study was aimed at investigating the pattern of chemokine receptor expression, including CCR1 to CCR3, CCR5 to CCR7, CXCR1 to CXCR5, and the migration ability of multiple myeloma (MM) plasma cells (PC). PC were recovered from the bone marrow (BM) of 29 MM patients, extramedullary sites of 10 patients and the BM of five controls. Flow cytometry analysis showed that the receptors mainly expressed on malignant B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…3). Similar to previous reports (18,43), we found that CXCR4 is overexpressed in cancer cells, in respectively 35% and approximately 69% of samples from AML and multiple myeloma patients, with expression levels of CXCR4 on blast cells and of plasmocytes higher than those of CD34 þ cells in healthy bone marrow samples, suggesting that hz515H7 should preferentially kill the neoplastic cells while preserving normal hematopoietic cells. Indeed, our in vitro results show that hz515H7 does not decrease the viability of B cells, monocytes, T cells, or NK cells, whereas rituximab, used as a positive control for ADCC (44) and CDC (40), leads to CD20 þ B-cell depletion as described previously (44,45).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…3). Similar to previous reports (18,43), we found that CXCR4 is overexpressed in cancer cells, in respectively 35% and approximately 69% of samples from AML and multiple myeloma patients, with expression levels of CXCR4 on blast cells and of plasmocytes higher than those of CD34 þ cells in healthy bone marrow samples, suggesting that hz515H7 should preferentially kill the neoplastic cells while preserving normal hematopoietic cells. Indeed, our in vitro results show that hz515H7 does not decrease the viability of B cells, monocytes, T cells, or NK cells, whereas rituximab, used as a positive control for ADCC (44) and CDC (40), leads to CD20 þ B-cell depletion as described previously (44,45).…”
Section: Discussionsupporting
confidence: 90%
“…Tumor tissues from at least 23 different types of human cancers of epithelial, mesenchymal, and hematopoietic origin express CXCR4 (4). Indeed, this receptor has been found to be overexpressed in a large number of cancers, including solid tumors (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), leukemia (17), multiple myeloma (18), and lymphomas (19). The CXCR4/SDF-1 axis is involved in cancer cell proliferation, in angiogenesis, and in antiapoptotic and metastases processes (20).…”
Section: Introductionmentioning
confidence: 99%
“…response to CXCL12. (10) This has been confirmed in a number of myeloma cell lines that showed a chemotactic response to CXCL12. (11) Thus, it is likely that stromal cell expression of CXCL12 plays a significant role in the progressive colonization of the skeleton during multiple myeloma progression.…”
mentioning
confidence: 77%
“…Several chemokines, including SDF-1, are produced by BM stromal cells and act as chemoattractants for MM cells. 13,14,[17][18][19]58,59 As a consequence, MM cells reside in the BM, where various cytokines produced in the microenvironment induce MM growth and survival. Hence, chemoattractants controlling homing of MM cells to the BM can be considered equally important for MM growth as the cytokines that provide the actual proliferative and antiapoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern of Ral activation was observed after SDF-1 stimulation of Ramos and Namalwa B-cell lines as well as primary human tonsillar B cells ( Figure 1C). Similar to normal plasma cells, 6,11,12 SDF-1 is a potent chemoattractant for MM cell lines 13,14,[17][18][19] and the malignant plasma cells from MM patients, 13,14,19,58,59 as illustrated by the ability of SDF-1 to induce migration of the MM cell lines NCI-H929 and OPM-1, and of primary MM cells, in the Transwell migration assay ( Figure 2A). In addition, for MM cells (cell lines and primary patient material), SDF-1 is acting exclusively as a true chemotactic factor, that is, migration occurred only when SDF-1 was present in the lower but not the upper compartment of the Transwells ( Figure 2A).…”
Section: Sdf-1 Induces Migration and Ral Activation In B Cells And MMmentioning
confidence: 99%